DEVELOPING SPEAKING SKILLS THROUGH INTERACTION STRATEGY TRAINING - Josephine Lourdunathan; Sujatha Menon (The English Teacher, 2005)
The introduction of the Malaysian University English Test (MUET) has led teachers to try new methods and strategies to improve students’ speaking skills. However, students are still unable to play an effective role in group discussions as they lack the necessary vocabulary and interaction strategies. This paper examines how interaction strategy training affects group interaction and task performance. For this purpose ten groups of students were introduced to and trained in the use of selected interaction strategies. The analysis indicated that training resulted in a significant use of interaction strategies, and in more effective interaction between group members.